2022
DOI: 10.17507/jltr.1303.12
|View full text |Cite
|
Sign up to set email alerts
|

A Change in Saudi Attitudes From Use of Euphemism to Taboo: A Sociolinguistic Study

Abstract: For this paper, we studied the use of linguistic taboo words in Saudi Arabian society. Three main taboo topics were addressed in the current study: the use of taboo words in social contexts, the use of taboo sex words, and the use of taboo swear words. A randomly chosen sample of 253 Saudi females from two different age groups participated in the study. A closed-ended multiple-choice questionnaire was used to collect the data. The findings provided considerable insights into the behavior of Saudi society. Saud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Moreover, Talley & Hui-ling (2012) also found that 41% of males use "A mixture of two or more languages for speaking taboo language" (p. 171), meaning that the students code-switch when using taboo language, which is the strategy 22.7% of this research participants use to avoid the explicit use of taboo expressions. Individuals' code-switching when uttering taboo expressions could be because they [1] find it easier to utter taboo language in a foreign/second language, as some foreign words can be lighter/easier to pronounce, and have less depth in meaning (to a non-native speaker) (than words in one's mother tongue), therefore cause less negative impact; emotional harm to the hearers' or/and social harm to their and face/reputation as "It is believed that a foreign word have less impact on the hearer than using a word in [one's] their native language" (Enab, 2020, p. 108), or [2] believe that the addressee will not fathom the meaning of the uttered foreign words, therefore these individuals will get to insult someone without the insulted person even realizing it, and by that causing more harm to the addressee's face (i.e., public self-image), or [3] because these foreign words sound fancy or show that one is educated or fluent in these languages, thus serve as a means of bragging or/and to create a certain social image [that the speaker desire to create for him/herself].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Talley & Hui-ling (2012) also found that 41% of males use "A mixture of two or more languages for speaking taboo language" (p. 171), meaning that the students code-switch when using taboo language, which is the strategy 22.7% of this research participants use to avoid the explicit use of taboo expressions. Individuals' code-switching when uttering taboo expressions could be because they [1] find it easier to utter taboo language in a foreign/second language, as some foreign words can be lighter/easier to pronounce, and have less depth in meaning (to a non-native speaker) (than words in one's mother tongue), therefore cause less negative impact; emotional harm to the hearers' or/and social harm to their and face/reputation as "It is believed that a foreign word have less impact on the hearer than using a word in [one's] their native language" (Enab, 2020, p. 108), or [2] believe that the addressee will not fathom the meaning of the uttered foreign words, therefore these individuals will get to insult someone without the insulted person even realizing it, and by that causing more harm to the addressee's face (i.e., public self-image), or [3] because these foreign words sound fancy or show that one is educated or fluent in these languages, thus serve as a means of bragging or/and to create a certain social image [that the speaker desire to create for him/herself].…”
Section: Discussionmentioning
confidence: 99%
“…The qualitative method will be used to provide information about conditions, situations, and events that occur in the present (Ross, 2005). The qualitative data will include [1] a collection of taboo expressions the researcher observed being used in Bahraini Arab society among young adult university students, in addition to [2] providing the religious, social, and cultural reasons for labeling the collected expressions as taboo, and [3] listing and discussing several [linguistic] strategies used to avoid the explicit, public use of taboo expressions. Furthermore, Fraenkel et al ( 2012) stated that "Ethnographic research also lends itself well to research topics that are not easily quantified" (p. 520).…”
Section: Data Collection Methodology and Procedures: 31 Methodologymentioning
confidence: 99%